The power of place : authentic learning through place-based education - Vander Ark, Tom; Liebtag, Emily; McClennen, Nate (Alexandria, VA : ASCD, 2020)
"The book offers a comprehensive and compelling case for place-based education and making communities the locus of learning for students of all ages and backgrounds"--
Preface: The future of place in learning -- An introduction to place-based education -- Why place matters -- Community as classroom -- Learner-centered -- Inquiry-based -- Local to global -- Design thinking -- Interdisciplinary -- A place-based education how-to guide.
Includes bibliographical references and index.
Donated by Teton Science & school Wyoming, Colorado States.
Keywords: Place-based education; Community and school